2006
DOI: 10.1158/1535-7163.mct-05-0431
|View full text |Cite
|
Sign up to set email alerts
|

The dietary flavonoid apigenin sensitizes malignant tumor cells to tumor necrosis factor–related apoptosis-inducing ligand

Abstract: Dietary flavonoid apigenin is expected to have preventive and therapeutic potential against malignant tumors. In this report, we show for the first time that apigenin markedly induces the expression of death receptor 5 (DR5) and synergistically acts with exogenous soluble recombinant human tumor necrosis factor -related apoptosis-inducing ligand (TRAIL) to induce apoptosis in malignant tumor cells. TRAIL is a promising candidate for cancer therapeutics due to its ability to selectively induce apoptosis in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 36 publications
(29 reference statements)
8
85
0
Order By: Relevance
“…A small number of similar studies with flavonoids in combination with TRAIL showed that apigenin, luteolin, quercetin and kaempferol synergistically induced apoptosis with TRAIL in human malignant tumor cells [20,[27][28][29][30]. Horinaka et al reported that luteolin increased TRAIL-induced apoptosis in HeLa cells through upregulation of death receptor TRAIL-R2 (DR5) [27].…”
Section: Resultsmentioning
confidence: 99%
“…A small number of similar studies with flavonoids in combination with TRAIL showed that apigenin, luteolin, quercetin and kaempferol synergistically induced apoptosis with TRAIL in human malignant tumor cells [20,[27][28][29][30]. Horinaka et al reported that luteolin increased TRAIL-induced apoptosis in HeLa cells through upregulation of death receptor TRAIL-R2 (DR5) [27].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several natural compounds, including dietary flavonoids, sensitize malignant tumor cells to TRAIL (40). The molecular basis for the sensitization of tumor cells by these agents may involve up-regulation of DR4/DR5 (41), down-regulation of the antiapoptotic molecules Bcl-2, Bcl-xL, and c-FLIP, or up-regulation of proapoptotic molecules, including Bax, caspases, and Fas-associated death domain (42).…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin also causes cell cycle arrest and sensitizes leukemia cells to vincristine (11). Apigenin has additionally been reported to induce apoptosis of prostate and colon cancer cells through induction of death receptor 5, and to act synergistically with exogenous tumor necrosis factor-related apoptosis-inducing ligand to induce cell apoptosis (12). Furthermore, apigenin enhances the anticancer activity or minimizes the resistance of cancer cells to a number chemotherapeutics, including gemcitabine, paclitaxel, 5-fluorouracil and doxorubicin by inducing apoptosis (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%